In situ assessment of the saliva effect on enamel morphology after microabrasion technique - Pini, Núbia Inocencya Pavesi; Lima, Débora Alves Nunes Leite; Sundfeld, Renato Herman [UNESP]; Ambrosano, Gláucia Maria Bovi; Aguiar, Flávio Henrique Baggio; Lovadino, José Roberto (Faculdade de Odontologia de Piracicaba - UNICAMP, 2014)
AIM:This study evaluated saliva effects on enamel morphology surface after microabrasion technique.METHODS:Enamel blocks (16 mm2) obtained from bovine incisors were divided into 9 groups as follows: one control group (no treatment), four groups with microabrasion treatment using 35% phosphoric acid and pumice (H3PO4+Pum) and other four groups treated with 6.6% hydrochloric acid and silica (HCl+Sil). One group of each treatment was submitted to 4 frames of saliva exposure: without exposure, 1-h exposure, 24-h exposure, and 7-days exposure on in situ regimen. Nineteen volunteers (n=19), considered as statistical blocks, used an intraoral appliance containing the specimens, for 7 days. Enamel roughness (Ra) was tested before and after treatment, and after saliva exposure. Confocal laser scanning microscopy (CLSM) was used to evaluate qualitatively the enamel morphology.RESULTS:All groups exhibited increased Ra after microabrasion. With regards to saliva exposure, the treatment with HCl+Sil presented more susceptibility to the saliva action, but no period of time was efficient in re-establishing this characteristic compared with the control group. CLSM analysis showed reduction of the micro-abrasive damages during the experimental times.CONCLUSIONS:Seven days of saliva exposure were not sufficient for the treated enamel to reach its normal characteristics compared with the control group.
Keywords: dental enamel; enamel microabrasion; saliva